Sentido ético da formação: implicações escolares - Leoni Maria Padilha Henning (EccoS – Revista Científica)
This proposal, since by its title, shows that it is broad and, why not, ambitious. However, what may seem defective, carries and makes explicit the necessary caution so that the treatment that a subject of this nature demands, in my opinion, should not be narrowed. The ethical sense of formation entangles anthropological, political, aesthetic aspects, among others, reflecting on the educational process as a whole. The text develops some of the themes involved in the central subject on the relations between Ethics and Education, trying to elucidate the impossibility of pretending to cleanse the human experiential field, removing the axiological questions. Hence, it presents some connections between Ethics, Aesthetics and Politics, among others, relating them to Education. In this scope of discussion, we place the school as one of the special places for the formation of people, hence requiring a demanding performance of teachers trained in a standard of philosophical-pedagogical excellence, about whose subjects we intend to present following the set of argumentation.